SUBSTRATES AND TEMPERATURES FOR GERMINATION AND VIGOR OF TOMATO SEEDS (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The establishment of the ideal conditions for germination, especially temperature and substrate, is of extreme importance, considering that these factors vary between seeds of different species. Thus, the objective of the present work was to define substrates and temperatures for germination of tomato seeds, IPA 6 cultivar. The work was conducted at the Laboratory of Seed Analysis, Department of Agrarian Sciences (DCA) of the State University of Montes Claros (UNIMONTES ). The experimental design was a completely randomized design, with the treatments distributed in a 2 x 5 factorial scheme, two temperatures (25 and alternating between 20-30 ° C) and five substrates: sand, sand + bovine manure (1: 1 ), sand + Bioplant® (1: 1), sand + organic compost (1: 1), and sand + vermiculite (1: 1) with four replicates of 50 seeds per treatment. The evaluated parameters were: germination, first germination count, germination speed index, seedling length, fresh and dry matter mass of seedlings. Under the conditions tested, it is concluded that the best conditions for conducting germination and vigor tests of tomato seeds are the sand, sand + Bioplant® and sand + vermiculite substrates and the temperature of 25 ° C.